Social mobilisation and political parties in Mexico - Lopez Garcia, A (2009)
This thesis examines the interactions between political parties and collective actors in the aftermath of regime change in Mexico. It describes different types of partnerships between parties and social organisations observed along a continuum ranging from more autonomous to less autonomous. Alliances were studied within and across levels of government and social sectors. The study found that the structure of political competition and the internal features of social organisations matter strongly in explaining variations in alliances between parties and organisations, as well as the use of unconventional or institutional tactics in achieving their goals within a partnership. These findings have thus implications for the literature on social mobilisation and political representation in new and developing democracies, where social movement actors’ have inaccurately been described as autonomous and opposed to political parties.